1985
DOI: 10.1111/j.1464-410x.1985.tb06299.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of Residual Urine: A Quantitative Method

Abstract: A method of measuring residual urine volume using ultrasound is described. The volume is computed from serial parallel sections of the bladder. This method is found to be significantly more accurate than previously reported techniques and is quick and easy to perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 12 publications
0
24
0
2
Order By: Relevance
“…In their investigation Doust et al [8] found an error percentage of 20%. In 1985, Beacock et al [10] found a good correlation in their patient group between the ultrasonically calculated volumes (also using the planimetric method) and the vol umes measured by catherization. Also in our patients the planimetric method gives more accurate results, but it is more time-consuming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their investigation Doust et al [8] found an error percentage of 20%. In 1985, Beacock et al [10] found a good correlation in their patient group between the ultrasonically calculated volumes (also using the planimetric method) and the vol umes measured by catherization. Also in our patients the planimetric method gives more accurate results, but it is more time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…It is not appropriate to compare results of different investigations, because: (a) Certain investigators applied the planimetric method to longitudinal sections [8], whereas others like Beacock et al [ 10] applied it to trans versal sections. Furthermore, in other methods de scribed the parameters are determined in different ways, (b) There is a great difference in image quality of differ ent ultrasonic equipment, depending on type and stage of development, (c) Every investigator has examined dif ferent populations.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [10] have also suggested the addition of a certain volume to get the most exact estimate of the residual urine volume. Furthermore, var ious reports cite a percentage of inaccuracy of 19-25.5% [14,[18][19][20]. Perhaps we should use the ellipsoid formula for only low residual urine volumes and utilize other parameters, such as width, height and depth [16] or sur face area [17], for high residual urine.…”
Section: Discussionmentioning
confidence: 99%
“…These examinations are more cumbersome than our technique and, thus require the child to be immobilization for longer periods. However they also share a high accuracy rate in the estimates 7 .…”
Section: Discussionmentioning
confidence: 99%